MORPHOLOGICAL AND PHYSICO-CHEMICAL PROPERTIES OF ERYTHROCYTE CARRIERS INCAPULATED BY TERPINEINDOLICALK ALOIDS - O. V. Trineeva; A. J. Halahakoon; A. I. Slivkin; E. E. Chupandina (Разработка и регистрация лекарственных средств)
Morphological and physico-chemical properties of erythrocytes encapsulated by terpenoindol alkaloids (TIA) by nephelometry and osmotic resistance of erythrocytes in a medium with low concentrations of sodium chloride have been studied. Changes in the morphological and physico-chemical parameters of TIA-loaded erythrocyte carriers and freshly isolated erythrocytes have been studied. It was found that during the process of encapsulation of TIA by a modified hypotonic swelling method, the morphological and physicochemical parameters of erythrocytes change insignificantly in comparison with the control.